Mitochondrial Activation and Reactive Oxygen-Species Overproduction during Sperm Capacitation are Independent of Glucose Stimuli - David F. Carrageta; Bárbara Guerra-Carvalho; Mário Sousa; Alberto Barros; Pedro F. Oliveira; Mariana P. Monteiro; Marco G. Alves (MDPI AG, 2020)
Spermatozoa capacitation is a complex process that requires specific ionic and energetic conditions to support biochemical alterations leading to motility hyperactivation. However, human sperm capacitation is still poorly understood. Herein, we studied the effects of glucose on human sperm capacitation. Healthy men seminal samples (n = 55) were submitted to a density gradient centrifugation and incubated in capacitating conditions in the absence or presence of increasing glucose concentrations (0, 5.5, 11, and 22 mM). Viability and total motility were accessed. Phosphotyrosine levels were measured. Mitochondrial activity and endogenous ROS production were evaluated. Oxidative stress-induced damage was analyzed. Culture media was collected and analyzed by 1H-NMR. Our results show that glucose is essential for human sperm capacitation and motility. Notably, we observed that mitochondrial activity increased even in the absence of glucose. This increased mitochondrial activity was followed by a ROS overproduction, although no oxidative stress-induced damage was detected. Our results show that glucose is essential for capacitation but mitochondrial activation is independent from its stimuli. ROS overproduction may take part on a finely regulated signaling pathway that modulates or even activates capacitation. Taken together, our results constitute a paradigm shift on human sperm capacitation physiology.